Codebook for rating clinical communication skills based on the Calgary-Cambridge Guide - Iversen, Else Dalsgaard (BMC Med Educ, 2020)
BACKGROUND: The aim of the study was to confirm the validity and reliability of the Observation Scheme-12, a measurement tool for rating clinical communication skills. METHODS: The study is a sub-study of an intervention study using audio recordings to assess the outcome of communication skills training. This paper describes the methods used to validate the assessment tool Observation Scheme-12 by operationalizing the crude 5-point scale into specific elements described in a codebook. Reliability was tested by calculating the intraclass correlation coefficients for interrater and intrarater reliability. RESULTS: The validation of the Observation Scheme-12 produced a rating tool with 12 items. Each item has 0 to 5 described micro-skills. For each item, the codebook described the criteria for delivering a rating from 0 to 4 depending on how successful the different micro-skills (or number of used jargon words) was accomplished. Testing reliability for the overall score intraclass correlation coefficients was 0.74 for interrater reliability and 0.86 for intrarater reliability. An intraclass correlation coefficient greater than 0.5 was observed for 10 of 12 items. CONCLUSION: The development of a codebook as a supplement to the assessment tool Observation Scheme-12 enables an objective rating of audiotaped clinical communication with acceptable reliability. The Observation Scheme-12 can be used to assess communication skills based on the Calgary-Cambridge Guide.